WHAT IS GOOD SCIENCE AND HOW FAR CAN IT GO? - Luis Fernando Aragón-Vargas (Pensar en Movimiento)
I have seized this opportunity to share with our readers a topic, seldom discussed among human movement professionals, which is nevertheless fundamental for our scientific endeavors:  philosophy of science.